Avaliação de glicerina bidestilada como agente viscosificante, tixotrópico e redutor de filtrado em fluidos base água compostos por argila bentonítica do tipo verde-lodo previamente beneficiada - Carvalho, Amanda Brito de (2020)
Purification and activation methods have proved to be excellent alternatives to improve the properties of less noble bentonite clays, in order to meet the needs of the market. Studies on alternative and biodegradable materials are progressively more present in the application of several industrial segments, for example drilling fluids area. Glycerin, in turn, is an environmentally friendly organic compound - a byproduct of the biodiesel generation process - and has very interesting properties, which make it very versatile and attractive for the oil industry. Thus, this work has as main objective to evaluate the effect of glycerin as a viscosifying agent, thixotropic and filtrate reducer in hydro-clay fluids. Parallel to this, to study the influence of physical, chemical and thermal treatments on the rheological properties and of mud-green clay filtrate - which will compose the glycerinated aqueous fluids. The clays underwent a purification process given in five physical steps and then were characterized physically, chemically and mineralogically. The characterizations, as well as the evaluation of VA, VP and VF, revealed efficiency of the purification method used. Only after physical purification, the VA values increased by 187.1%, PV by 57.1% and the VF decreased by 21.1%. Then, different combinations of Na2CO3 concentration and heat treatments were performed. After analysis of VA, VP and VF, the combination of 100 mEq aged for 24 hours at room temperature was chosen for the formulation of the fluid with glycerin additive. Finally, the mass proportions of 0: 100, 10:90, 20:80, 30:70; 40:60 and 50:50 m glycerin / m water were tested in the preparation of fluids. The rheological, filtrate and pH properties were analyzed. It was observed that glycerin performed the functions of viscosifying agent, thixotropic and filtrate reducer, and that the sludge behaved as pseudoplastic with flow limit, well adjusted to the Herschel-Bulkley model (R2> 0.99). The presence of 50% w / w of the additive glycerin caused an increase in VA (40%), in VP (320%), thixotropy (2.300%), in addition to a 65% reduction in VF